Ambiguous representations: power and mimesis in colonial Guinea - Carvalho, Clara (2002)
This paper explores some aspects of the ambiguity of power relations during the colonial period that still influence the postcolonial construction of the nation. The colonial encounter led to the confrontation of local political institutions with the colonial project of cultural and political hegemony. Local intermediaries were particularly sensitive to this mutual game of domination, integration and exclusion. Focusing on the iconographic representations of a category of such intermediaries, the régulos or local chiefs in Guinea-Bissau – both from the local point of view and from the colonialist one – we have access to a mirror of the empire: the perverse and continual negotiation of identities and references between colonizers and colonized.